2019
DOI: 10.1016/j.heliyon.2019.e02341
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular effects of dorsiflexor training with and without blood flow restriction

Abstract: Blood flow restriction training (BFRT) has been proposed for elderly and clinical populations with weakness. Before being used in these populations it is important to understand the neurological effects of, and subject perceptions to, BFRT. Seventeen healthy subjects were recruited and performed 2 experimental sessions, BFRT and training without blood flow restriction (TR-only), on separate days. Four sets of concentric/eccentric dorsiflexion contractions against theraband resistance were performed. Surface el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 53 publications
(75 reference statements)
1
16
0
Order By: Relevance
“…These differences were still apparent after the end of the 4-min period. Since then, similar observations were reported by several research groups (Kinugasa et al, 2006 ; Lauver et al, 2017 , 2019 ; Husmann et al, 2018 ; Ilett et al, 2019 ; Kjeldsen et al, 2019 ). Even though the results of the latter studies indicated profound increases in muscle excitation with LL-BFR, there was also a small number of studies which could not find any between-group differences (Thiebaud et al, 2014 ; Oranchuk et al, 2019 ).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…These differences were still apparent after the end of the 4-min period. Since then, similar observations were reported by several research groups (Kinugasa et al, 2006 ; Lauver et al, 2017 , 2019 ; Husmann et al, 2018 ; Ilett et al, 2019 ; Kjeldsen et al, 2019 ). Even though the results of the latter studies indicated profound increases in muscle excitation with LL-BFR, there was also a small number of studies which could not find any between-group differences (Thiebaud et al, 2014 ; Oranchuk et al, 2019 ).…”
Section: Discussionsupporting
confidence: 80%
“…The results regarding the differences in muscle excitation between LL and LL-BFR training demonstrated a significant increase in surface muscle EMG in favor of LL-BFR. The longitudinal changes which are reviewed in this work, resemble findings from cross-sectional studies looking at the acute effects of training with partial vascular occlusion (Kinugasa et al, 2006;Lauver et al, 2017Lauver et al, , 2019Husmann et al, 2018;Ilett et al, 2019;Kjeldsen et al, 2019). In a frequently cited study by Moritani et al (1992) participants were instructed to complete a 4-min bout of repeated intermittent isometric hand grip contractions (20% MVC) with one group having the blood flow restricted during the second minute (cuff pressure 200 mmHg).…”
Section: Muscle Excitationmentioning
confidence: 85%
See 2 more Smart Citations
“…There is a new training model, namely by blocking the flow of blood, there will be a bigger contraction if this method is used (Kjeldsen, Naess-Schmidt, Hansen, Nielsen, & Stubbs, 2019), this exercise is done by tying the muscles, it is uncomfortable, is more painful and has a higher level of fatigue (Kjeldsen et al, 2019). Based on research exercise improves arterial blood vessel function even without weight loss (Maeda et al, 2015).…”
Section: Introductionmentioning
confidence: 99%